Crosstalk Analysis of SiC Ultraviolet Single Photon Avalanche Photodiode Arrays - Heng Zhang; Linlin Su; Dong Zhou; Weizong Xu; Fangfang Ren; Dunjun Chen; Rong Zhang; Youdou Zheng; Hai Lu (IEEE Photonics Journal)
Optical crosstalk is one of major problems limiting the performance of focal plane arrays based on single photon avalanche diodes (SPADs). In this work, for the first time the crosstalk characteristics of a 4H-SiC SPAD linear array are studied, which is based on a real-time dual channel data acquisition method. It is found that SiC SPAD array exhibits similar crosstalk probability compared with those of InGaAs-based SPAD arrays, which can be effectively reduced by trench isolation between adjacent pixels or by lowering overbias. The average time required for forming a crosstalk event is determined between 7 and 10 ns. As a result, active time-gated operation scheme can be applied for reducing crosstalk.